Mapping glacier-related research in polar regions: a bibliometric analysis of research output from 1987 to 2016. Issue 1 (1st January 2018) - Liang, Qi; Peng, Sha; Niu, Beibei; Zhou, Chunxia; Wang, Zhen
ABSTRACT: We carried out a bibliometric analysis of literature related to glaciers in polar regions from the period 1987–2016 indexed in the Science Citation Index Expanded database. A comprehensive review was performed by analysing the research output trends, publication categories, main journals, leading countries and their collaborations, leading scientists, author keywords and Keywords Plus. The results indicated that the number of publications related to glaciers in polar regions has increased rapidly. The USA and several European countries, including the UK, France, Germany and Switzerland, are the leaders in the field of glacial studies, as reflected both in the productivity measures and in the distribution of core scientists. Quaternary Science Reviews, the Journal of Glaciology, and Geophysical Research Letters were the most productive journals for glacial studies. The synthesized analysis of the keywords demonstrated the current research emphases and hinted at future research trends. Reconstructing past climate changes through studies of ice-core records is one of the most important research subjects. Numerical modelling has become a commonly used tool in polar region glacial research. A better understanding of the responses of glaciers to widespread climatic warming is needed now and in the future.